Growth factors and glucose homeostasis in diabetic rats: effects of exercise training - Gomes, Ricardo Jose [UNESP]; Curiacos de Almeida Leme, Jose Alexandre [UNESP]; de Moura, Leandro Pereira [UNESP]; de Araujo, Michel Barbosa [UNESP]; Rogatto, Gustavo Puggina [UNESP]; de Moura, Rodrigo Ferreira [UNESP]; Luciano, Eliete [UNESP]; Rostom de Mello, Maria Alice [UNESP] (John Wiley & Sons Ltd, 2009)
To investigate the alterations of glucose homeostasis and variables of the insulin-like growth factor-I (IGF- 1) growth system in sedentary and trained diabetic (TD) rats, Wistar rats were divided into sedentary control (SC), trained control (TC), sedentary diabetic (SD), and TD groups. Diabetes was induced by Alloxan (35 mg kg(-1) b.w.). Training program consisted of swimming 5 days week(-1), 1 h day(-1), during 8 weeks. Rats were sacrificed and blood was collected for determinations of serum glucose, insulin, growth hormone (GH), IGF-1, and IGF binding protein-3(IGFBP-3). Muscle and liver were removed to evaluate glycogen content. Cerebellum was extracted to determinate IGF-1 content. Diabetes decreased serum GH, IGF-1, IGFBP-3, liver glycogen, and cerebellum IGF-1 peptide content in baseline condition. Physical training recovered liver glycogen and increased serum and cerebellum IGF-1 peptide in diabetic rats. Physical training induces important metabolic and hormonal alterations that are associated with an improvement in glucose homeostasis and serum and cerebellum IGF-1 concentrations. Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: diabetes; glucose homeostasis; insulin-like growth factor-I; training